MORE THAN MEETS THE EYES: THE LENS OF VISIBILITY IN INTERNET RESEARCH - Myles, David; Trottier, Daniel; Millette, Mélanie; Bonneau, Claudine; Sergi, Viviane; Casemajor, Nathalie; Toupin, Sophie (AoIR Selected Papers of Internet Research, 2018)
The objective of this panel is to examine the analytical and empirical relevance of the “visibility lens” for Internet research. In the past decade, researchers have started to take a specific interest in the constitutive role of online visibility in the organization of social reality. Studies have underlined the fundamental role of visibility afforded by digital technologies in the social recognition or exclusion of individuals, groups, and communities. They have also identified visibility and its management as being constitutive of social identities, relations, and practices among actors in a variety of fields. So far, Internet researchers have provided various definitions and operationalizations of online visibility. For example, visibility can be apprehended as both a political lever for individuals and collectives or as a conceptual category for researchers to make sense of social reality. Visibility is also frequently associated with digital materiality. As such, it is sometimes used as a criterion to categorize digital technologies regarding the control they allow for users to manage and disclose personal contents or activities. Furthermore, visibility can also be conceptualized as an affordance that is enabled by the functionalities of digital technologies and enacted through their situated uses. In this panel, presenters will raise theoretical, methodological, and ethical issues linked to visibility by drawing from a series of case studies. They will then draw similarities and contrasts between cases, as well as discuss the implications and, indeed, the relevance of formalizing the lens of visibility in the field of Internet research.